Automated analysis of multi-channel EEG in preterm infants. Issue 9 (September 2015) - Murphy, Keelin; Stevenson, Nathan J.; Goulding, Robert M.; Lloyd, Rhodri O.; Korotchikova, Irina; Livingstone, Vicki; Boylan, Geraldine B.
Highlights Automatic detection of burst and interburst periods in multi-channel preterm EEG. EEG marked by 3 independent observers, detailed interobserver analysis. Mathematical features of the EEG are calculated and correlated with gestational age.